2021
DOI: 10.3390/app11083454
|View full text |Cite
|
Sign up to set email alerts
|

Development of Technological Capabilities through the Internet of Things (IoT): Survey of Opportunities and Barriers for IoT Implementation in Portugal’s Agro-Industry

Abstract: The agro-industrial sector consumes a significant amount of natural resources for farming and meat production. By 2050, population growth is expected, generating more demand and, consequently, more consumption of scarce resources. This challenging scenario is a concern of the European Commission, revealed in the Green Deal commitment and by the United Nations’ 12th goal of sustainable development. Thus, organizations must increase productivity and be more sustainable as soon as possible. Internet of Things (Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The study results show that the framework can control the productivity and prognosis of production lines by converting collected data into useful data information. Gaspar et al [66] investigated the internet of thing's technological capabilities by surveying small, micro, and agro-food industries. The results of the study demonstrate that several opportunities for internet of things solutions include mainly monitoring and measuring variables of production, which can help managers make precise decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study results show that the framework can control the productivity and prognosis of production lines by converting collected data into useful data information. Gaspar et al [66] investigated the internet of thing's technological capabilities by surveying small, micro, and agro-food industries. The results of the study demonstrate that several opportunities for internet of things solutions include mainly monitoring and measuring variables of production, which can help managers make precise decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the apparel industry, Bizuneh and Tadesse ( 2022 ) indicated that technological innovation such as the computer-aided design system is important in reducing waste. MSMEs could adopt internet of things to be eco-efficient, avoid food loss and waste, and improve production (Gaspar et al 2021 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…This suggestion aligns with de Sousa Jabbour et al ( 2020 ). Another significant area for future research in MSMEs is to explore the role of internet of things in WM and the challenges of its adoption (Elkhwesky and Elkhwesky 2022 , alkhwesky 2022 ; Gaspar et al 2021 ).…”
Section: Agenda and A Call For Future Researchmentioning
confidence: 99%
“…Internet of things (IoTs) and artificial intelligence (AI) applications have contributed significantly to the rise of precision agriculture and its application in the agriculture sector (Ayaz et al 2019 ; Hosseinnia Shavaki and Ebrahimi Ghahnavieh 2022 ; Kwaghtyo and Eke 2022 ; Wang et al 2021 ;). Notably, utilizing IoTs, physical objects are easily identified and tracked by gathering relevant data, which will be turned into fruitful information and disseminated over a network (Gaspar et al 2021 ). Accordingly, since alerts can be created for agricultural situations that need corrections, IoTs effectively plan and control agricultural processes (Farooq et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As per IoTs, unmanned aerial vehicles (UAVs), namely drones, which are aircraft where there is not any human pilot on board, are one of the most versatile devices (Gaspar et al 2021 ). UAVs are able to resolve the drawbacks in the physical IoT infrastructure already established (Srivastava and Prakash 2022 ).…”
Section: Introductionmentioning
confidence: 99%